Overrange protection electronic scale - LI SHU; FENG JUMENG (2013)
The utility model relates to an overrange protection electronic scale, including a scale pan, a weighing sensor unit, a signal acquisition and conversion unit, an MCU control unit, a display/input/alarm unit and an overrange protection unit. The weighing sensor unit is in mechanical connection with the weighing pan. The weighing sensor unit is in electric signal connection with the signal acquisition and conversion unit. The display/input/alarm unit comprises an LCD liquid crystal display circuit, a key input circuit and a sound and light alarm circuit. The MCU control unit is respectively in electric signal connection with the signal acquisition and conversion unit, the LCD liquid crystal display circuit, the key input circuit, the sound and light alarm circuit, and the overrange protection unit. The overrange protection electronic scale has a small size, is low in power consumption and direct in operation, can display the current weight and the remaining measuring weight, ensures the precision of the electr